2021
DOI: 10.1111/jvim.16104
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bacterial and fungal populations in urine from clinically healthy dogs using next‐generation sequencing

Abstract: Background: Urine from clinically healthy dogs is not sterile. Characterizing microbial diversity and abundance within this population of dogs is important to define normal reference ranges for healthy urine.Objectives: To establish composition and relative representation of bacterial and fungal microbiomes in urine of clinically healthy dogs. Animals: Fifty clinically healthy dogs.Methods: Analytic study. Urine sampling via cystocentesis. Comprehensive evaluation of urine including standard urinalysis, cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…In this study, the four most abundant phyla in urine were Firmicutes, Actinobacteria, Bacteroides, and Proteobacteria. These phyla also dominate the urine microbiota in humans [17,36,38,40,44,45] and have been reported in previous studies on healthy dog urine [80,81]. In humans, taxa associated with UC vary widely across studies, but Acinetobacter and Actinomyces have been found at increased abundances in patients with UC across at least three studies [35,42,44].…”
Section: Urine and Fecal Microbiota Associated With Ucsupporting
confidence: 62%
“…In this study, the four most abundant phyla in urine were Firmicutes, Actinobacteria, Bacteroides, and Proteobacteria. These phyla also dominate the urine microbiota in humans [17,36,38,40,44,45] and have been reported in previous studies on healthy dog urine [80,81]. In humans, taxa associated with UC vary widely across studies, but Acinetobacter and Actinomyces have been found at increased abundances in patients with UC across at least three studies [35,42,44].…”
Section: Urine and Fecal Microbiota Associated With Ucsupporting
confidence: 62%
“…There are only two studies, to our knowledge, on the healthy canine urine microbiota. Both employed cystocentesis for sampling, and microbial diversity did not differ by sex [ 56 , 57 ]. Hormones have also been linked to changes in the fecal microbiome of women and could feasibly be altering the urine microbiota [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dogs are a valuable translational model for many human diseases, including urogenital diseases like bladder cancer [55]. However, there have only been two studies, to our knowledge, characterizing canine urine microbiota [56,57] and none evaluating canine urine DNA extraction methods. Multiple methods of urine microbial DNA isolation have been reported in human studies [12,51,[58][59][60][61], and there are a few studies that have compared microbial DNA extraction methods.…”
Section: Introductionmentioning
confidence: 99%
“…In the only two studies of the canine bladder microbiome, genera belonging to the family Xanthomonadaceae were commonly detected in the urine of healthy dogs. Melgarejo et al ( 16 ) detected Xanthomonas , along with Stenotrophomonas and Bradyrhizobium . Burton et al ( 15 ) also detected Xanthomonadaceae , but when we reanalyzed their sequence data using the bioinformatics protocols used in this study, most of them were assigned to Bradyrhizobium and Stenotrophomonas , and none were assigned to Xanthomonas .…”
Section: Discussionmentioning
confidence: 99%
“…Given the proven existence of the urinary microbiome in humans and dogs ( 15 , 16 ), it seems reasonable to hypothesize that a feline urinary microbiome also exists and may interact differently with the host depending on the health of the urinary system. Certainly, subclinical bacteriuria is not uncommon in cats ( 17 ), and urinary tract diseases, notably CKD and feline idiopathic cystitis (FIC), are common causes of morbidity and mortality in cats.…”
Section: Introductionmentioning
confidence: 99%